Recovery of Cerium Dioxide from Spent Glass-Polishing Slurry and Its Utilization as a Reactive Sorbent for Fast Degradation of Toxic Organophosphates. (16th September 2015) - Janoš, Pavel; Kuráň, Pavel; Ederer, Jakub; Šťastný, Martin; Vrtoch, Luboš; Pšenička, Martin; Henych, Jiří; Mazanec, Karel; Skoumal, Miroslav
Abstract : The recovery of cerium (and possibly other rare earth elements) from the spent glass-polishing slurries is rather difficult because of a high resistance of polishing-grade cerium oxide toward common digestion agents. It was shown that cerium may be extracted from the spent polishing slurries by leaching with strong mineral acids in the presence of reducing agents; the solution may be used directly for the preparation of a ceria-based reactive sorbent. A mixture of concentrated nitric acid and hydrogen peroxide was effective in the digestion of partially dewatered glass-polishing slurry. After the removal of undissolved particles, cerous carbonate was precipitated by gaseous NH3 and CO2 . Cerium oxide was prepared by a thermal decomposition of the carbonate precursor in an open crucible and tested as reactive sorbent for the degradation of highly toxic organophosphate compounds. The samples annealed at the optimal temperature of approximately 400°C exhibited a good degradation efficiency toward the organophosphate pesticide fenchlorphos and the nerve agents soman and VX. The extraction/precipitation procedure recovers approximately 70% of cerium oxide from the spent polishing slurry. The presence of minor amounts of lanthanum does not disturb the degradation efficiency.